Public Communication Strategies on Socialization Covid-19 Vaccine in Indonesia Perspective Sociology of Mass Communication - Clara Gynada Winshine; Haryono Haryono (Green Publisher Indonesia, 2021)
To hold a Covid-19 event, of course, it requires first socialization to the community. So that people can believe that it has been confirmed to be safe and has gone through the III clinical trial by PT. Bio Farma (Persero). This study aims to determine the public communication strategy for the socialization of the COVID-19 vaccine carried out by the government which is studied in the perspective of the Sociology of Mass Communication. This study uses a library research method that refers to resources available both online and offline such as: scientific journals, books and news sourced from trusted sources. The results of this study conclude that handling and overcoming COVID-19 is still a top priority in Indonesia and still requires serious attention. Especially in the process of socializing the COVID-19 vaccine and the process of educating the public still needs to be done, considering that there are still groups of people who refuse vaccination for unscientific reasons.